TYPOLOGY OF LEGAL RESEARCH METHODS IN NORMATIVE AND SOCIOLOGICAL THINKING - Ujang Charda S (SEAN Institute, 2021)
Legal Research Methods in understanding and exploring technical aspects of legal research in accordance with the peculiarities of legal science which has a dual paradigm, not only normative in character, but also with sociological empirical character. The research method used is descriptive analytical with a normative juridical approach through the literature and field research stages with data collection techniques through library research. Then the data were analyzed through a qualitative normative method without using numbers and mathematical formulas. Based on the results of the study, it shows that the dichotomy of the scientific paradigm of legal science has actually resulted in a lack of agreement among legal scientists regarding the legal research model that will be developed to answer various legal issues that arise in the life of the legal community. This dual legal scientific paradigm also ultimately creates confusion regarding the research model that will be developed when conducting legal research